Analysis of Students' Creative Thinking Ability in Solving Problems on Mts Yaspi-Punti Flat Figure Material - Siska Dwi Astiati, Ilham, Siska; Ilham, Ilham (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Analysis of Students' Creative Thinking Ability in Solving Problems on Mts Yaspi-Punti Flat Figure Material. The aim of the research is to explore and describe the mathematical creative thinking abilities of class VII MTs YASPI-Punti students in solving problems on flat shapes. The type of research is descriptive research. Meanwhile, the approach is a qualitative approach. Research subjects are based on the level of mathematical creative thinking ability, namely high creative, medium creative and low creative categories. Data was obtained using written test instruments. The analysis technique uses qualitative descriptive analysis techniques. The results of the research show that subjects with the ability to think creatively can easily solve problems well without any difficulty at all so that subjects with creative abilities can fulfill the four indicators of creative thinking ability easily, namely Fluency, Flexibility, Originality and Details (Elaboration). Subjects with less creative abilities cannot expand an idea and detail an answer. So it is concluded that subjects with sufficient creative abilities can only fulfill the three indicators of creative thinking ability, namely Fluency, Flexibility and Originality. Subjects with non-creative abilities can only describe the shape of questions in finding the area of a square, while subjects cannot develop questions in various rectangular shapes. Cannot understand and solve questions well and clearly from various types of quadrilaterals and cannot expand an idea and detail an answer. So it can be concluded that subjects with non-active abilities can only fulfill one Fluency indicator.